Epidemiology of soil transmitted helminth and Strongyloides stercoralis infections in remote rural villages of Ranomafana National Park, Madagascar. (17th February 2019) - Hakami, Lee; Castle, Paul M.; Kiernan, Jaydon; Choi, Koeun; Rahantamalala, Anjanirina; Rakotomalala, Emma; Rakotoarison, Rado; Wright, Patricia; Grandjean Lapierre, Simon; Crnosija, Ivan; Small, Peter; Vigan-Womas, Ines; et al.
ABSTRACT: Soil-transmitted helminth (STH) infections carry the highest number of disability adjusted life years among all neglected tropical diseases, disproportionately affecting low-income countries such as Madagascar.  This study describes the epidemiology of STH and S. stercoralis infections in twelve remote villages surrounding Ranomafana National Park (RNP), Ifanadiana, Madagascar. Questionnaires and stool samples were collected from 574 subjects from random households. The Kato-Katz method and spontaneous sedimentation technique were used to examine stool samples for evidence of infection. Infection prevalence rates were 71.4% for Ascaris lumbricoides (95% CI: 67.7–75.1), 74.7% for Trichuris trichiura (95% CI: 71.1–78.2), 33.1% for hookworm (95% CI: 29.2–36.9), and 3.3% for Strongyloides stercoralis (95% CI: 1.84–4.77). Participants who were older in age (OR = 0.96; 95% CI: 0.95–0.99) and who had a high school education (OR = 0.17; 95% CI: 0.04–0.77) were less likely to be infected with a STH. Females were less likely to be infected with A. lumbricoides (OR = 0.52; 95% CI: 0.33–0.82). Participants living in villages further from the main road were more likely to be infected with a STH (F = 4.00, p = 0.02). Overall, this study found that 92.5% (95% CI: 90.3–94.6) of the people living in rural regions near RNP have at least one STH infection. This calls into question the current preventative chemotherapy (PC) program in place and suggests that further medical, socioeconomic, and infrastructural deveopments are needed to reduce STH prevalence rates among this underserved population.